Ophthalmic, Hearing, Speaking and School Readiness Outcomes in Low Birth Weight and Normal Birth Weight Primary School Children in Mashhad-Iran - Ashraf Mohammadzadeh; Mohsen Jafarzade; Ahmad Shah Farhat; Rana Amiri; Habiballah Esmaeli (Acta Medica Iranica, 2011)
Low Birth weight infants are at risk of many problems. Therefore their outcome must evaluate in different ages especially in school age. In this study we determined prevalence of ophthalmic, hearing, speaking and school readiness problems in children who were born low birth weight and compared them with normal birth weight children. In a cross-sectional and retrospective study, all Primary School children referred to special educational organization center for screening before entrance to school were elected in Mashhad, Iran. In this study 2400 children enrolled to study and were checked for ophthalmic, hearing, speaking and school readiness problems by valid instrument. Data were analyzed by SPSS 11.5. This study showed that 8.3% of our population had birth weight less than 2500 gram. Visual impairment in LBW (Low Birth Weight) and NBW (Normal Birth Weight) was 8.29% vs. 5.74% and there was statistically significant difference between them (P=0.015). Hearing problem in LBW and NBW was 2.1% vs. 1.3 and it was not statistically significant. Speaking problem in LBW and NBW was 2.6% vs. 2.2% and it was not statistically significant. School readiness problem in LBW and NBW was 12.4% vs. 5.8% and it was statistically significant (P<0.001). According to the results, neurological problems in our society is more than other society and pay attention to this problem is critical. We believe that in our country, it is necessary to provide a program to routinely evaluate LBW children.